Penciptaan Prototipe Locomotif Dari Barang Bekas Menjadi Karya Seni Bernilai Ekonomis - Wahyu Hidayat (CandraRupa : Journal of Art, Design, and Media, 2019)
This research is the creation of works of art that have an orientation for creative-based industries, in this study more focused on the process of creating artworks by responding to used materials in the environment around us by prioritizing aesthetic values ​​in the artwork, the works produced are not only limited to decoration or functional only but also contains content that has a purpose and a specific purpose from its creator which among other things is also capable of growing the value of the creative economy.